ISLAMIC BANK CONSUMERS IN JAVA - THE HERO, THE DUPE, THE SNOB, OR THE SOCIALLY RESPONSIBLE - Rajiani, Ismi (UiTM, 2012)
In the early 2000s, Islamic banking evolved as a new model of Indonesia’s financial institutions. However, in practice, there have been significant differences between countries that have been successful in applying Islamic banking and those that have not. This article is aimed at exploring the applicability of Islamic banking in a particular cultural context. In particular, the study analyses the applicability of Islamic banking in Indonesia, mainly in East Java where most Muslims are found. A cultural theory is presented whereby Islamic banking is depicted as a culturally dependent strategy. The study proposes that the successful implementation of Islamic banking requires complementary between the reform strategies that are adopted and the particular cultural characteristics of the country in which they are implemented.